Comparative Genomic Analysis Uncovered Evolution of Pathogenicity Factors, Horizontal Gene Transfer Events, and Heavy Metal Resistance Traits in Citrus Canker Bacterium Xanthomonas citri subsp. citri - Huang, Chien-Jui; Wu, Ting-Li; Zheng, Po-Xing; Ou, Jheng-Yang; Ni, Hui-Fang; Lin, Yao-Cheng (Frontiers in Microbiology, 2021)
Background: Worldwide citrus production is severely threatened by Asiatic citrus canker which is caused by the proteobacterium Xanthomonas citri subsp. citri. Foliar sprays of copper-based bactericides are frequently used to control plant bacterial diseases. Despite the sequencing of many X. citri strains, the genome diversity and distribution of genes responsible for metal resistance in X. citri subsp. citri strains from orchards with different management practices in Taiwan are not well understood. Results: The genomes of three X. citri subsp. citri strains including one copper-resistant strain collected from farms with different management regimes in Taiwan were sequenced by Illumina and Nanopore sequencing and assembled into complete circular chromosomes and plasmids. CRISPR spoligotyping and phylogenomic analysis indicated that the three strains were located in the same phylogenetic lineages and shared ~3,000 core-genes with published X. citri subsp. citri strains. These strains differed mainly in the CRISPR repeats and pathogenicity-related plasmid-borne transcription activator-like effector (TALE)-encoding pthA genes. The copper-resistant strain has a unique, large copper resistance plasmid due to an unusual ~40 kbp inverted repeat. Each repeat contains a complete set of the gene cluster responsible for copper and heavy metal resistance. Conversely, the copper sensitive strains carry no metal resistance genes in the plasmid. Through comparative analysis, the origin and evolution of the metal resistance clusters was resolved. Conclusion: Chromosomes remained constant among three strains collected in Taiwan, but plasmids likely played an important role in maintaining pathogenicity and developing bacterial fitness in the field. The evolution of pathogenicity factors and horizontal gene transfer events were observed in the three strains. These data suggest that agricultural management practices could be a potential trigger for the evolution of citrus canker pathogens. The decrease in the number of CRISPR repeats and pthA genes might be the result of adaptation to a less stressful environment. The metal resistance genes in the copper resistant X. citri strain likely originated from the Mauritian strain not the local copper-resistant X. euvesicatoria strain. This study highlights the importance of plasmids as ‘vehicles’ for exchanging genetic elements between plant pathogenic bacteria and contributing to bacterial adaptation to the environment.